Variación de ingresos del Comercial "Dos Corazones" del Cantón Urdaneta Parroquia Ricaurte de los periodos 2020 – 2021. - Córdova Gavica, Diana Milena (2023)
The company "Dos Corazones" is dedicated to the wholesale sale of plastic articles and is in the Urdaneta Canton, Ricaurte Parish. During the periods 2020-2021, this company has experienced a decrease in its income due to the Covid-19 pandemic and the government-imposed restrictions. By studying the variation in income at "Dos Corazones" during the 2020-2021 period, a greater understanding can be gained of how external factors, such as confinement, affect a company's income. This is important because this information can be used to help managers make optimal financial decisions. The main objective of the research is to evaluate the variation of the income of the Commercial "Dos Corazones" during the period 2020-2021 and use financial indicators to make decisions in case any problems are found in the financial statements. A quantitative methodology will be applied in this research to analyze the financial situation of the company "Dos Corazones" during the periods 2020-2021. Numerical and statistical data from the company's financial statements will be collected and analyzed using techniques such as vertical analysis, horizontal analysis, and financial ratio analysis. In addition, an interview will be conducted with the financial manager of the company to obtain complementary information and deepen relevant aspects related to financial management.